A Aplikasi E-Surat Desa Berbasis Web untuk Optimalisasi Layanan Administrasi Desa: Optimalisasi Pelayanan Administrasi Desa Melalui Aplikasi E-Surat Berbasis Web - Alvin Rainaldy Hakim; Indra Lina Putra; Andre Tri Saputra; Rizqi Miftakhul Ulum (Fakultas Teknik Universitas Persada Indonesia YAI, 2026)
Village administrative services often face challenges in terms of efficiency, transparency, and data accuracy, especially in letter management processes that are still performed manually. This condition results in longer service times and difficulties in document tracking. This study aims to design and implement a Web-Based Village E-Letter Application to optimize village administrative services through an efficient and transparent digital system. The development method used is the Waterfall model, which includes stages of requirement analysis, system design, implementation, testing, and maintenance. The application was developed using PHP as the programming language, MySQL as the database system, and HTML, CSS, and Bootstrap for creating a responsive and user-friendly interface. The implementation results show that the e-letter application improves the efficiency of letter creation and archiving processes compared to the previous manual system. Moreover, it enhances transparency and public accessibility to village administrative services. Therefore, this web-based e-letter application serves as an effective solution to support the digital transformation of village governance towards a more modern and accountable administration